Usage of Vitagenic Technologies at Regilion Studies Lessons - Blazhevych, Yurii (Pedagogical Discourse, 2013)
Based on the documentary, archival and religion studies materials the questions of the usage of vitagenic technologies at the lessons of religion studies on the topic "Religion and Morality. Religious Symbols" are elucidated. It defines the methods of vitagenic technology usage in the classroom, puts an emphasis on the major stages of religious morality, provides comparative analysis of ethical principles and rules of various confessions, describes peculiarities of the mentioned topic. During the lesson the group of students was divided into subgroups that received spcifically developed tasks and was tested accordingly. At the end of the lesson the students were asked to self-evaluate their participation in the classroom and to express their thoughts considering personal experience.